Study of Anatomical Variations of Nose and Para-nasal Sinuses in Computed Tomography Scan - Pokhrel, Sona; Pandey, Bhuwan Raj (Journal of KIST Medical College, 2020)
Introduction: Computed tomography (CT) has nowadays become the investigation of choice for diagnosis and evaluation of anatomical variations of the nose and paranasal sinuses. Methods: A cross sectional study was conducted in the Department of Radiology of Lumbini Medical College Hospital from June 2019 to May 2020. Total of 130 patients were enrolled for the study. All patients were subjected to Siemens Somatom scope 16 slice CT scan. Each scan was studied for the presence of agger nasi cell, concha bullosa, deviated nasal septum, haller cell, onodi cell, uncinate process variation and type of olfactory fossa. Results: The mean age of patients was 36. 86 ±12.06 years. There were 76 males (58.5%) and 54 females (41.5%) with male: female ratio of 1.4:1 with highest range in age group of 31 to 45 years (46.9%). Anatomical variation between male and female was statistically not significant (p>0.05). The most common anatomical variation noted was nasal septal deviation (73.1%), then agger nasi cell (59.3%), concha bullosa (24.6%), paradoxical medial turbinate (7.7%), onodi cell (6.9%), uncinate process variation (5.4%) and least was haller cell (4.6%). Most of the scans had more than one anatomical variation, which was statistically significant (p<0.05). The most common type of olfactory fossa depth was Keros type II (61.5%). Conclusion: Computed tomography of the paranasal sinus has improved the visualization of anatomical variation hence radiologist must pay close attention to variants.